Colossians remixed: subverting the empire - Walsh, Brian J. (Downers Grove InterVarsity Press, 2004)
Have we really heard the message of Colossians? Is this New Testament book just another religious text whose pretext is an ideological grab for dominating power? Reading Colossians in context, ancient and contemporary, can perhaps give us new ears to he
Keywords: Bible. -- Colossians -- Social scientific criticism. Bible. -- Colossians. Social scientific criticism of sacred works. Bible. -- N.T. -- Colossians -- Social scientific criticism. Rome -- In the Bible. Globalization -- Religious aspects -- Christianity